Assessing learning eﬀectiveness through Learning Management Systems: trends from the last five years - Rahmadani, Moza Nindy; Sandy, Teguh Arie; Ni’mah, Noorma Khoirun; Rohmania, Wafa Lauhatur; Sari, Setyaisah Nurmala (Universitas Negeri Semarang, 2024)
This study analyses the inﬂuence of the Learning Management System (LMS) on learning eﬀectveness through bibliometric analysis over the past 5 years. Using Scopus and VOSViewer data, this study explores publicaton trends, journal and author contributons, and key topics in LMS research. Results show increased publicatons, with a peak of 219 documents in 2023. IEEE Access is the leading journal, and Computer Science dominates with 23.1% of publicatons. Two main clusters with 15 topics were identfed, “Learning System” being the focus. This research provides a comprehensive insight into the development of LMS in modern educaton and potental directons for future studies, contributng to the understanding of the role of LMS in improving the quality of educaton in the digital era.